2007
DOI: 10.1111/j.1365-2133.2007.08209.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 1 receptor (MC1R) genotype influences erythemal sensitivity to psoralen–ultraviolet A photochemotherapy

Abstract: Our data demonstrate that MC1R genotype influences PUVA erythemal sensitivity in patients with psoriasis and other common skin diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For example, in our own work we have shown that polymorphisms in the gene for the drug metabolising enzyme and antioxidant, glutathione-S transferase M1, which is null in 50% of Caucasians, are associated with erythemal sensitivity to UVB, as assessed by MED and also in a separate study, with plasma psoralen levels and PUVA minimal phototoxic dose (MPD) and thus, at least in part, contribute to individual erythemal sensitivity to UVB and PUVA (16,17). We have also seen an association between polymorphisms in the melanocortin-1 receptor (MC1R) and PUVA erythemal sensitivity, as assessed by MPD (18).…”
Section: Mechanismsmentioning
confidence: 61%
See 1 more Smart Citation
“…For example, in our own work we have shown that polymorphisms in the gene for the drug metabolising enzyme and antioxidant, glutathione-S transferase M1, which is null in 50% of Caucasians, are associated with erythemal sensitivity to UVB, as assessed by MED and also in a separate study, with plasma psoralen levels and PUVA minimal phototoxic dose (MPD) and thus, at least in part, contribute to individual erythemal sensitivity to UVB and PUVA (16,17). We have also seen an association between polymorphisms in the melanocortin-1 receptor (MC1R) and PUVA erythemal sensitivity, as assessed by MPD (18).…”
Section: Mechanismsmentioning
confidence: 61%
“…It is certainly likely that there are individual risk factors for photosensitivity and skin cancer with drugs that we do not fully understand, and whether P450s or other drug metabolising enzymes, transporters or antioxidants can be implicated in some instances should be considered. Other possible culprits are melanocortin 1 receptor (MC1R) polymorphisms, which have been shown to subtly influence PUVA erythemal sensitivity, as has the glutathione S transferase, GST M1 (16)(17)(18)211). Patients who are null for the GST M1 gene have higher serum 8-MOP concentrations after standard oral doses of 8-MOP and lower PUVA MPDs, reflecting increased photosensitivity (17).…”
Section: Drug-induced Phototoxicity and Photocarcinogenesismentioning
confidence: 99%
“…The truncated Mc1r receptor in the recessive yellow mouse, where the ability to engage cAMP is totally absent, differs from the human polymorphisms in MC1R which encode a complete receptor, albeit one with altered function. In humans there is conflicting evidence on correlation between MC1R genotype and erythema (26,27) and between MC1R genotype and immune responses (12,28). Most studies have focussed on the anti-inflammatory properties of α-MSH from which a role for MC1R in UV sensitivity has been inferred.…”
Section: Discussionmentioning
confidence: 99%
“…Some MC1R alleles have been associated with fair skin, increased sensitivity to ultraviolet (UV) radiation (the 'so-called RHC phenotype associated with RHC variants), psoralen-UVA photochemotherapy erythemal sensitivity, a worse outcome of melanoma patients treated with anti-BRAF and increased skin cancer risk. [4][5][6][7][8][9] Nevertheless, its role in skin inflammatory diseases, as compared to non-psoriatic controls, has not been previously described.…”
Section: Editormentioning
confidence: 99%